News writing - McKane, Anna (Los Angeles SAGE, 2014)
The ability to hone and craft an eye catching news story is fundamental to good journalism. It is an essential skill that all journalists must carry with them. The growth of online journalism and of social media has meant that the skills required in news writing are evolving, opening up fresh challenges and exciting new possibilities.
1. What makes news? -- 2. Gathering the news -- 3. The effective intro -- 4. The inverted pyramid -- 5. News as a conversation -- 6. Make it a new story, not a narrative -- 7. Presentation and headlines -- 8. Other ways into the story-- 9. Accuracy and getting it right -- 10. Choosing the right words -- 11. Writing for clarity -- 12. Grammar and punctuation -- 13. More news models -- Epilogue -- Appendix -- Glossary -- Further reading -- Index
Keywords: Journalism -- Authorship; Reporters and reporting; Mass media -- Authorship; Report writing